Influence of UV radiation-absorbing foils on secondary plant metabolites in three lettuce cultivars (Lactuca sativa L. and Cichorium intybus L.) - Laurenčíková, Nikola; Živčák, Marek; Neugart, Susanne; Pöhnl, Tobias (Frontiers in Food Science and Technology, 2023)
Introduction: Providing fresh and healthy vegetables, produced locally and under climate-friendly conditions, is a major challenge for future agriculture. The usage of foil tunnels prolongs cultivation periods in colder climates and reduces abiotic and biotic stress factors during crop growth, but it may also affect nutritional value and consumer perception due to the altered light spectrum. Methods and results: Three different foils, one with low UV transmission, another with reduced UVB transmission, and a control foil with high UV transmission, were used to modulate light conditions for three different lettuce cultivars [radicchio type (cv. Indigo), romaine type (cv. Attico), and butterhead type (cv. Larissa)]. Taste-relevant sesquiterpene lactones and health-relevant carotenoids and polyphenols were measured by high-performance liquid chromatography, which revealed that light conditions are widely irrelevant for carotenoid concentrations. However, when UV-shielding foils were used, there was an up to 66% decrease in total polyphenol concentration. Less reduction could be achieved through the use of partially UV-transmissive foils. Sesquiterpene lactone concentrations were higher in plants under UV-blocking foils, when radicchio-type lettuce, naturally rich in sesquiterpene lactones, was cultivated. Discussion: It is noteworthy that the sesquiterpene lactone lactucopicrin had a negative correlation with UVB intensities, while lactucin was unaffected. The nutritional value, measured by three different antioxidant activity assays, also benefited from an optimized foil choice with higher UV transmission.